Quality, improvement of soluble dietary fiber from Dictyophora indusiata by-products by steam explosion and cellulase modification: Structural and functional analysis - Mengfan Lin; Changrong Wang; Wenfei Wu; Qingsong Miao; Zebin Guo (Food Chemistry: X)
Steam explosion (SE) and cellulase treatment are potentially effective processing methods for Dictyophora indusiata by-products, for use in high-value applications. The treatment conditions were optimized by response surface methodology, increasing the soluble dietary fiber (SDF) yield by 1.52 and 1.16 times after the SE and cellulase treatments, respectively. The both treatments did not affect the functional groups and crystal types of the polysachharides, but both reduced the crystallinity. The SDF had a porous microstructure, which would increase the specific surface area and facilitates the adsorption of water and glucose, thereby improving its functional properties. SE and cellulase treatment significantly improved the hydration capacity of SDF; the glucose adsorption capacity increased by 1.15 and 1.07 times, respectively. Overall, the modified SDF showed different degrees of advantages in terms of yield, physicochemical and functionality. This study demonstrated that SE and cellulase are effective modification methods for SDF made from D. indusiata by-products.